The Predictive Value of Neutrophil/Lymphocyte Ratio for CK-MB Elevation in Myocardial Infarction: A Study in Syrian ACS Patients - Yusuf, Issa; Ibrahim, Rama (Jordan Journal of Pharmaceutical Sciences, 2025)
Acute coronary syndrome (ACS) is a serious cardiovascular condition associated with a high mortality rate. It typically arises from the rupture of an atherosclerotic plaque leading to thrombus formation and encompasses unstable angina (UA) and myocardial infarction (MI). The latter results in myocardial necrosis, which triggers an acute inflammatory response that contributes to disease progression. Few studies have explored the diagnostic utility of the neutrophil-to-lymphocyte ratio (NLR) as a complementary, inexpensive, and easily performed test for diagnosing MI, either alone or in conjunction with creatine kinase-MB (CK-MB). Therefore, this study aimed to evaluate the diagnostic accuracy of admission NLR as a biomarker for MI in ACS patients. This cross-sectional study included 89 patients with ACS who were admitted to the emergency department of Al-Basel Hospital between March 2023 and January 2024. The patients were categorized into two groups: MI (n = 41) and UA (n = 48). Baseline characteristics and specific inflammatory markers (WBC, neutrophils, lymphocytes, and NLR) were assessed and compared between the two groups. Our findings revealed that admission NLR values were significantly higher in the MI group compared to the UA group (4.62 vs. 2.56, P < 0.01). Moreover, NLR was significantly correlated with CK-MB activity in the MI group (r = 0.45, P < 0.01). A cutoff value of 2.78 for admission NLR yielded a sensitivity of 73% and a specificity of 62% for predicting MI in ACS patients. Notably, combining CK-MB and NLR measurements improved diagnostic performance, with a sensitivity of 88% and specificity of 93%. These findings suggest that a simple biomarker such as NLR could serve an adjunctive role in facilitating the diagnosis of MI in patients with ACS.